Answers

2015-01-04T17:27:31+08:00
1st equation:
I'll eliminate the x, well it depends on you though.
2x-3y=-4     -- >    2x-3y=-4       
-2(x-y=-3)   -- >    -2x+2y=6        Multiply the second equation by -2.
                                 -y =2       Add the equations.
                                  y=-2       
Replace y with -2 in either equation to determine the value for x.

2x-3y=-4  -- > 2x-3(-2)=-4
                     2x+6=-4
                     2x=-4-6
                     2x=-10
                       x= -5

Therefore, the solution is (-5,-2)

0